Evaluation of immune response following one dose of an AS03A-adjuvanted H1N1 2009 pandemic influenza vaccine in Japanese adults 65 years of age or older - Hideyuki Ikematsu; Kazuyoshi Tenjinbaru; Ping Li; Anuradha Madan; David Vaughn (Human Vaccines & Immunotherapeutics, 2012)
Objective: This study assessed the immunogenicity, long-term persistence of immune response and safety of a single dose of an A/California/07/2009 H1N1 pandemic influenza vaccine adjuvanted with AS03 (α-tocopherol and squalene based oil-in-water emulsion Adjuvant System) in subjects ≥ 65 y of age (NCT01114620).Results: At Day 21, the HI immune response met all three European guidance criteria [seroconversion rate (SCR): 60.0%; seroprotection rate (SPR): 64.0%; geometric mean fold rise (GMFR): 10.2] and the US guidance criterion for SCR. At month 6, the HI immune response against the A/California/07/2009 H1N1 strain persisted but at levels lower than that observed at Day 21 (SCR: 38.8%; SPR: 42.9%; HI antibody geometric mean titer: 27.6); the European regulatory guidance criteria for SCR and GMFR were still met. Overall, the vaccine was well-tolerated.Conclusion A single dose of the 3.75µg HA AS03-adjuvanted H1N1 2009 pandemic vaccine induced immune responses against the vaccine strain that met the European regulatory guidance criteria at day 21 in the elderly Japanese population; the immune response persisted at lower levels at month 6. No safety concerns were identified. These results suggest that two vaccine doses might be useful for the elderly population to improve antibody induction and persistence.Methods: In this open-label, single group study, 50 subjects received one dose of the 3.75 µg hemagglutinin (HA) AS03-adjuvanted H1N1 2009 vaccine. Immunogenicity assessments were made before vaccination, 21 days and six months after vaccination using hemagglutination inhibition (HI) and microneutralization assays. Immunogenicity end points were based on US and European regulatory criteria.